CHRONIC ILLNESS MANAGEMENT: THE ROLE OF FAMILY SUPPORT AND SOCIAL SERVICES - Sonia; Asma Bibi; Shaher Bano (International Journal of Contemporary Issues in Social Sciences, 2024)
The purpose of the research paper is to explore the complex inter-related processes and factors relating to the management of chronic illnesses within family care and social work services. This is why chronic illnesses are difficult for individuals as well as their families and the society at large to manage and how supportive and social services network can help in this struggle. Using both qualitative and quantitative approaches, this work aims to explore the key challenges and opportunities as well as the best practices in providing family support and social services effective for the quality of life in chronic illnesses. Through exploring the mechanisms and outcomes of family support and social services for people with chronic illnesses, this study can help healthcare providers and policy makers as well as program practitioners for developing ideal models of practice.